PENGGUNAAN ENZIM LIPASE RHIZOPUS ORYZAE DAN ASPERGILLUS NIGER DALAM PEMBUATAN GLISERIDA KAYA ASAM LEMAK OMEGA-3 MINYAK IKAN LEMURU - Ichda Chayati (Teknologi dan Kejuruan, 2012)
Abstract: This research was aimed to observe the performance of lipase from Rhizopus oryzae and Aspergillus niger in hydrolyzing sardine oil in order to get high omega-3 glycerides. Hydrolysis were carried out in 1 g of sardine oil, 1 ml of phosphate buffer, reciprocal waterbath shaker 100 strokes/minute, temperature 37 oC, 200 U for both of lipase for 12 hours. The triglyceride, diglyceride, monoglyceride, and free fatty acid contents as the products of the 12 h hydrolysis with lipase from R. oryzae were 37, 21, 7, and 35%, respectively, and 55, 21, 8, and 16% with lipase from A. niger, respectively. Both lipases made 40% increasingly in the EPA content of triglyceride. Hydrolysis of sardine oil by lipase from R. oryzae increased 70% of DHA in the triglyceride and 100% in the mixture of mono- and diglyceride. By lipase from A. niger, DHA in the triglyceride and in the mixture of mono and diglyceride increased 50 and 25%, respectively.